First record of orcas (Orcinus orca) preying on a prickly shark (Echinorhinus cookei) in the Gulf of California: insights into shark ecology - Lara-Lizardi, Frida; Gómez, María Fernanda; Quintero-Perez, Andrea (Frontiers in Fish Science, 2025)
The first documented instance of predation on a prickly shark (Echinorhinus cookei) by orcas (Orcinus orca) in the shallow waters of the southwestern Gulf of California, particularly around Cerralvo Island, is presented. The observation was made possible through a combination of local ecological knowledge and citizen science efforts, demonstrating the value of community involvement in marine research. Both the vulnerability of prickly sharks to industrial fishing and the deep- water sharks limited ecological knowledge in the Gulf of California emphasize the significance of this sighting. The findings underscore the necessity for ongoing research and conservation efforts, highlighting the importance of the integration of the local ecological knowledge and citizen science to protect this species' habitat in the Gulf of California and beyond.